La importancia de los personajes en el diseño narrativo: la figura de Lanark / Thaw como elemento de análisis en la obra de Alasdair Gray Lanark - Díaz Martínez, Mario (Estudios Humanísticos. Filología, 1995)
The contemporary literary critics have seriously questioned the role iayed by the characters in the narrativa discourse of today. However, if we adopt a literary approach opened to the idea of intertextuality as a general principie (which is also based on the postmodernist textual theories), it is possible to apply the same phenomena to the network of relationships established between the very characters of a work, as a starting point to analizo the work in which they exist. After stating briefly these theoretical conceps from the point of view of well-known scholars, we move on towards the figure of the main character in Alasdair Gray’s Lanark, analizing its importante in the wide context of the fiction discourse. So, Lanark/Thaw, as a single entity composed by two «realities», reveals itself as a figure with a strong intra-textual component, that is, with a double existente n two diffetent levels of conscioussness. We also detail its relationsips with other minor characters which populate the worlds of Lanark, and finally we are capable to explain its influence in the work as a whole.